2018
DOI: 10.1055/s-0038-1625978
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Middle Turbinate Concha Bullosa and its Relationship with Chronic Sinusitis: A Prospective Radiologic Study

Abstract: Introduction  A pneumatized turbinate, also called concha bullosa, is a normal anatomical variant of the paranasal sinus region. Depending on the site of pneumatization, the concha is classified into extensive, bulbous or lamellar type. The middle turbinate concha bullosa has been implicated as a possible etiological factor in chronic sinusitis. Objectives  The aim of this study was to investigate the anatomical variations of the concha bullosa, based on paranasal sinus imaging, and its possible association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…The third most common anatomical variant is concha bullosa which was found in 87 study population with prevalence of 43.5% of cases. In our study there is no statistical relation of concha bullosa with sinusitis which has insignificant p value of 0.6.This is in correlation with another recent study done in Mar 2018 by Raja Kalaiarasi et al 35 The study was done to investigate the variations of the concha bullosa, based on paranasal sinus imaging, and its possible association with sinusitis. The study concluded that there was no statistically significant association between any types of middle turbinate concha with sinusitis.…”
Section: Discussionsupporting
confidence: 82%
“…The third most common anatomical variant is concha bullosa which was found in 87 study population with prevalence of 43.5% of cases. In our study there is no statistical relation of concha bullosa with sinusitis which has insignificant p value of 0.6.This is in correlation with another recent study done in Mar 2018 by Raja Kalaiarasi et al 35 The study was done to investigate the variations of the concha bullosa, based on paranasal sinus imaging, and its possible association with sinusitis. The study concluded that there was no statistically significant association between any types of middle turbinate concha with sinusitis.…”
Section: Discussionsupporting
confidence: 82%
“…The present study has adopted the definition by Zinreich et al, 37 who have considered any pneumatization degree as CB and was found in 61.4% of the scans (Figure 1 b). Other studies have found a prevalence of 30.6% by Alsowey et al, 32 31.7% by Kalaiarasi et al, 36 30% and 51% by two different studied in Turkey. 6,29 The middle turbinate usually curves medially toward the nasal septum.…”
Section: Discussionmentioning
confidence: 77%
“…Concha bullosa (CB) is one of the most frequently found anatomic variants. The incidence of CB in the population ranges from 13 to 73% in literature; 36 the differences reported may have been influenced by the aeration degree, and lower rates suggest that only large turbinates may have been taken into consideration. The present study has adopted the definition by Zinreich et al, 37 who have considered any pneumatization degree as CB and was found in 61.4% of the scans (Figure 1 b).…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of pneumatization of the MT is between 13 and 53.6% (8). CB is usually asymptomatic and diagnosed incidentally by CT. From time to time, an over-pneumatized MT can lead to deviated nasal septum, contact headache, nasal obstruction, and sinusitis (9).…”
Section: Introductionmentioning
confidence: 99%